TANAMAN BIOFARMAKA DI LINGKUNGAN SEKOLAH SMP PGRI BATURRADEN KABUPATEN BANYUMAS SEBAGAI UPAYA PELESTARIAN KEARIFAN LOKAL - Indriani, Anisa; Laila Rahayu, Nur; Falah, Muhammad (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Biopharmaceutical plants are kinds of horticultural plants that are used as medicinal ingredients, spices, cooking spices and natural base ingredients in cosmetics. Other terms for bio-pharmaceutical plants are medicinal plants, live pharmacies, and TOGA. The importance of applying local wisdom about biofarmaceutical plants to students as an effort to preserve the learning environment in schools can be more meaningful if the application and experience of biofarm plants is practiced in the practical life of everyday life. The aim is to acquire student understanding of the type of biopharmaceutical plant by knowing its types and can analyze the conditions and efforts of maintenance of bio-farm plant as a local knowledge. The methods used in this research are surveys, campaigns, questionnaires, and school citizens' interviews around the knowledge of bio-pharmaceutical plants. With results as much as 60% of PGRI Baturraden high school students already know about bio-pharmaceutical plants.The bio-pharmaceutical plants planted in Baturraden are aloe vera, ginger, red ginger (Zingiber officinale var. rubrum), dlingo (Acorus calamus), turmeric (Curcuma longa), celery (Apium graveolens), and spruce. (Kaempferia galanga).Maintenance efforts for bio-pharmaceutical plants are carried out through the stages of inserting material, sorting, education, plant layout arrangement, watering, and fertilization. The condition of bio-pharmaceutical plants prior to maintenance indicates that some plants are poorlyined, but after the maintenance efforts of untreated biopharmaceuticals have been reduced.